Psychological distress and internet-related behaviors between schoolchildren with and without overweight during the COVID-19 outbreak - Chen, Chao-Ying; Chen, I-Hua; O'Brien, Kerry S; Latner, Janet D; Lin, Chung-Ying (International Journal of Obesity, 2021)
The novel coronavirus disease 2019 (COVID-19) pandemic, and its resulting social policy changes may result in psychological distress among schoolchildren with overweight. This study thus aimed to (1) compare psychological distress (including fear of COVID-19 infection, stress, anxiety, and depression), perceived weight stigma, and problematic internet-related behaviors between schoolchildren with and without overweight; (2) assess whether perceived weight stigma and problematic internet-related behaviors explained psychological distress. Schoolchildren (n = 1357; mean age = 10.7 years) with overweight (n = 236) and without overweight (n = 1121) completed an online survey assessing their fear of COVID-19 infection, stress, anxiety, depression, perceived weight stigma, problematic smartphone application use, problematic social media use, and problematic gaming. Schoolchildren with overweight had significantly higher levels of COVID-19 infection fear, stress, depression, perceived weight stigma, and problematic social media use than those without overweight. Regression models showed that perceived weight stigma and problematic internet-related behaviors were significant predictors of psychological distress among schoolchildren with overweight. Strategies to manage perceived weight stigma and problematic internet-related behaviors may have a positive influence on mental health among schoolchildren with overweight under health-threatening circumstances, such as the current COVID-19 pandemic.